2004
DOI: 10.3354/dao059205
|View full text |Cite
|
Sign up to set email alerts
|

Viral gametocytic hypertrophy caused by a papova-like virus infection in the Pacific oyster Crassostrea gigas in Korea

Abstract: During a routine survey of the Pacific oyster Crassostrea gigas in Tongyoung (previously Chungmu) on the southern coast of Korea, basophilic inclusions were observed in the gonadal tissues. They were detected from March to May at a prevalence rate of 3.3 to 7.1%. The inclusion bodies were Feulgen-positive and stained orange-red with phloxine tartrazine. Electron microscopic observation revealed non-enveloped, icosahedral particles 40 to 45 nm in diameter. These morphological characteristics resemble those of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 5 publications
7
16
0
Order By: Relevance
“…In the present study we observed between 3 and 14 infected cells per section in 3 female oysters; however, the number of oysters examined is too low to establish infection rate or infection intensity. In common with other studies (Choi et al 2004, Garcia et al 2006, no haemocytic reaction was observed in the present study, suggesting limited health implications for the infected oysters. However, Garcia et al (2006) comment that gamete viability and consequently oyster fecundity could be altered by VGH.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…In the present study we observed between 3 and 14 infected cells per section in 3 female oysters; however, the number of oysters examined is too low to establish infection rate or infection intensity. In common with other studies (Choi et al 2004, Garcia et al 2006, no haemocytic reaction was observed in the present study, suggesting limited health implications for the infected oysters. However, Garcia et al (2006) comment that gamete viability and consequently oyster fecundity could be altered by VGH.…”
supporting
confidence: 69%
“…Farley (1976Farley ( , 1985 described a papova-like virus in hypertrophied gametocytes of the eastern oyster Crassostrea virginica; since then other authors have reported similar conditions in various oyster species in North America, Asia and Europe (McGladdery & Stephenson 1994, Elston 1997, Choi et al 2004, Garcia et al 2006. This is the first report of VGH in C. gigas in Ireland.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Ultrastructural examination of inclusion body material from one affected male showed arrays of intranuclear icosahedral virus-like particles (Fig. 5C) 38 to 40 nm in diameter, consistent with a virus previously described as causing hypertrophied gametocytes (ovacystis) in eastern Crassostrea virginica (Farley 1976, Winstead & Courtney 2003 and Pacific (Choi et al 2004, Garcia et al 2006 oysters. The same inclusion bodies or other known types of virus-associated cytopathology were not observed (Table 2) in any of the juvenile or adult oysters examined from the other farm sites listed in Table 1.…”
Section: Papilloma-or Polyoma-like Virusmentioning
confidence: 86%
“…The condition was first described in ova of Crassostrea virginica from the Piscataqua River, Maine, USA (Farley 1976(Farley , 1978. Papovavirus, causing gametogenic or other cellular hypertrophy, has subsequently been reported in C. virginica from the Gulf of Mexico (Winstead & Courtney 2003) and Atlantic Canada (McGladdery & Stephenson 1994), in C. gigas from Korea (Choi et al 2004), France (Garcia et al 2006), Germany (Watermann et al 2008) and Ireland (Cheslett et al 2009), in the golden-lipped pearl oyster Pinctada maxima from Torres Strait, Australia (Norton et al 1993), in the softshell clam Mya arenaria in Massachusetts, USA, and Ruditapes philippinarum from Spain (Elston 1997, Montes et al 2001. Similar examples of unconfirmed virus-associated gametogenic hypertrophy have been reported in other ostreid species including Saccostrea glomerata, C. rhizophorae, Ostrea edulis and Ostreola conchaphila (Farley 1978, Bower et al 1994.…”
Section: Discussionmentioning
confidence: 99%